The spiritual well-beinig of Filipino youth in selected high schools in Cavite: A religious interpretation - Entegro, Eunice Ann E. (Animo Repository, 2020)
This study discussed the spiritual well-being vis-à-vis spirituality of adolescents in the Philippines. Two hundred (200) Filipino adolescents, ages thirteen to eighteen, responded to the survey. Using the Spiritual Health and Life-Orientation Measure (SHALOM) of John Fisher, the data results were analyzed in the lenses of the interpretative approach of Philip Sheldrake. SHALOM data were analyzed using the Mann-Whitney U Test and Statistical Package for the Social Sciences (SPSS). The qualitative analysis discussed the Filipino adolescents' spiritual well-being as exhibited in their experiential relationship with themselves, others, the environment, and the transcendent. This was connected with the religious experience of ascetical-monastic, mystical, active-practical, and prophetic-critical. In general, Filipino adolescents' spiritual well-being is positive. They live in harmony within their relationships in the personal, communal, environmental, and transcendental domains. The differences between the four domains are not too far from each other, except for the transcendental domain, which is remarkably high. It was also found that adolescents without behavioral problems have a deeper and more encompassing understanding of the ideal and lived spiritual well-being than adolescents with behavioral issues. The results show that there is a relationship between school behavioral problems and spiritual well-being. This study hopes to contribute to the vast literature on spirituality and well-being. Keywords – adolescents experiences, behavioral problems, spiritual well-being, SHALOM